2002
DOI: 10.1001/jama.288.17.2136
|View full text |Cite
|
Sign up to set email alerts
|

Crosswalk Markings and the Risk of Pedestrian–Motor Vehicle Collisions in Older Pedestrians

Abstract: Crosswalk markings appear associated with increased risk of pedestrian-motor vehicle collision to older pedestrians at sites where no signal or stop sign is present to halt traffic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(72 citation statements)
references
References 14 publications
6
62
1
2
Order By: Relevance
“…However, it is worth noting that previous studies have also observed negative impacts of marked crosswalks on pedestrian safety, 20,21 at unsignalized and uncontrolled locations (no traffic signals or stop signs), 22,24,25 for older pedestrians 24 and on multi-lane roads with high traffic volumes. 25 This result still highlights the fact that marked crosswalks at major urban intersections need complementary measures, such as appropriate medians and pedestrian signals with exclusive phases (e.g., "All red") to really protect crossing pedestrians.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it is worth noting that previous studies have also observed negative impacts of marked crosswalks on pedestrian safety, 20,21 at unsignalized and uncontrolled locations (no traffic signals or stop signs), 22,24,25 for older pedestrians 24 and on multi-lane roads with high traffic volumes. 25 This result still highlights the fact that marked crosswalks at major urban intersections need complementary measures, such as appropriate medians and pedestrian signals with exclusive phases (e.g., "All red") to really protect crossing pedestrians.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have suggested that well-marked crosswalks and pedestrian crossing signs may improve pedestrian or motorist behaviour. 18,19 However, marked crosswalks have been associated with more injured pedestrians, [20][21][22][23] including older people 24 as well as those injured on multi-lane roads with high traffic volumes. 12,25 Major roads have been associated with pedestrian injuries for decades, mainly as a proxy of traffic volume.…”
mentioning
confidence: 99%
“…Although evidence exists of reduced effectiveness of specific road design features for older adults, this has not been well studied in children. 65 More rigorous study of these features with further spatial analysis is required to better ascertain the safety effects for children.…”
Section: Comparisons Of Findings To Previous Studiesmentioning
confidence: 99%
“…(Koepsell et al, 2002). 91 If the accidents are occurring at lower speeds then vehicle occupant fatalities per accident may not increase but pedestrian deaths per accident will.…”
Section: 54c Estimates Of Pedestrian Fatality Equations -No Seatmentioning
confidence: 99%